Amphitropical disjunctive species in the complex thalloid liverworts (Marchantiidae). (2nd January 2017) - Gradstein, S. Robbert
Abstract : Plant disjunctions between the temperate regions of the northern and southern hemisphere, commonly called amphitropical or bipolar disjunctions, have been discussed by numerous authors but very little attention has been paid to the occurrence of such disjunctive ranges in the complex thalloids (Marchantiidae). A perusal of the literature revealed 20 species of Marchantiidae with amphitropical ranges, in eight genera ( Asterella, Clevea, Corsinia, Cryptomitrium, Oxymitra, Riccia, Riella and Sphaerocarpos ). These amphitropical species are distributed in subtropical and Mediterranean regions of the northern and southern hemisphere but not, or rarely, in the tropics. The majority are disjunctive between North America and southern South America and between Eurasia and South Africa. Long-distance dispersal of spores via birds is considered the most plausible natural cause of these amphitropical ranges. About two-third of the species have bisexual spores, which should be advantageous to long-distance dispersal. Extinction due to past climatic fluctuations may also have played a role but fossil evidence is lacking. A few species have attained their amphitropical range by human-mediated introduction: Riccia warnstorfii Limpr. and Sphaerocarpos texanus Austin were presumably introduced in the southern hemisphere whereas S. stipitatus Bisch. ex Lindenb. from Central Chile and South Africa is adventive in the northern hemisphere. The amphitropical ranges exhibited by a number of complex thalloid species are solely based on morphological, floristic and ecological evidence and have not been tested by molecular analysis. Careful comparisons of the northern and southern populations based on an integrated molecular-phylogenetic, morphological-anatomical and chemical approach should be carried out.